The role of school physical education on adolescents' fitness levels during the pandemic period from COVID-19: An observational study of the Italian scientific high school—section sport and physical activity - Patti, Antonino; Giustino, Valerio; Figlioli, Flavia; Miceli, Matteo; Barca, Martina; Drid, Patrik; Palma, Antonio; Bianco, Antonino (Frontiers in Public Health, 2022)
Objectives In Italy, in 2013, a new school curriculum with a sport character was established in high schools, called Sports High School (SHS). The aims of this study were: (1) to assess the fitness levels of SHS students who, respecting all the safety rules to limit the spread of COVID-19, practiced physical education (PE) at school with continuity for almost all of 2021, and to compare them with Traditional High School (THS) students; (2) to evaluate as the SHS may have influenced the fitness levels in adolescents. Methods This is a case-control study in which thirty participants were enrolled (SHS: n = 15; THS: n = 15). To assess the fitness levels, the following tests were administered: the Static Baropodometric and Stabilometric Analyses, the Counter Movement Jump (CMJ), and the Handgrip test. All these tests were administered when the non-pharmaceutical interventions (NPIs) for COVID-19 allowed the resumption of PE lessons (T0) and 2 months after their resumption (T1). Results Unpaired t-test between SHS (T0) vs. THS (T0) showed significant differences between: Handgrip test Dx and Handgrip test Sx (both p < 0.001), Surface Sx foot and Surface Dx foot (both p < 0.05), and CMJ (p < 0.001). These results were also confirmed in T1. The performance analysis between T0 and T1 of both SHS and THS showed improvements in SHS: Handgrip test Dx (p < 0.05; d = 0.57), Handgrip test Sx (p < 0.01; d = 0.87), and CMJ (p < 0.05; d = 0.59). Pearson's analysis of the results of the tests showed significant strong correlations between: Handgrip test Dx and Handgrip test Sx (R = 0.959; p < 0.001), Handgrip test Dx and CMJ (R = 0.881; p < 0.001), Handgrip test Sx and CMJ (R = 0.893; p < 0.001). The same analysis showed significant but moderate correlations between: Surface foot Sx and CMJ (R = 0.489; p < 0.01), Surface foot Sx and y-mean (R = 0.485; p < 0.01), Surface foot Dx and CMJ (R = 0.444; p < 0.05). Conclusions This study is in agreement with the literature showing that the quarantine period and the NPIs for COVID-19 caused a decrease in fitness levels in adolescents. Our results showed that students of SHS recorded higher strength performance both in the Handgrip test and in the CMJ.